Penerapan Video Animasi Pembelajaran Pendidikan Agama Islam Kelas 4 di SD Al-Ittihad Pekanbaru - Dewi, Meillany; Kartina Diah Kusuma Wardani; Suhatman, Rahmat; Kamila, Aida (Fakultas Teknik Universitas Lancang Kuning, 2021)
There are many factors that influence the achievement of learning objectives, one of which is learning media. With the use of appropriate learning media, it can make learning more effective so that teachers can create a new, conducive atmosphere among students and something that cannot be presented or raised in class can be presented clearly and easily understood by students.This PKM aims to facilitate the school, especially SDIT AL-Ittihad Pekanbaru, to make learning materials in the form of animated videos as an alternative to existing learning media. This PKM produces animated videos to assist teachers in delivering Al fatihah and Asmaul Husna (Allah SWT Almighty and Allah SWT Most Giver) materials to grade 4 elementary school students so that they can become alternative learning media in schools so that they can become alternative learning media in schools. This activity received a very good response and enthusiasm from the school and from grade 4 elementary school students, so as to improve good relations between PCR and SDT AL-Ittihad Pekanbaru.